Teacher Factors as Correlates of Social Studies Students Creativity Skills Development in Upper Basic Schools, Kwara State - AYODEJI, Adeyemi (Ilorin Journal of Education, 2025)
Education is a crucial tool for intellectual, social, moral, spiritual, political, and economic development. This study examined teacher factors as correlates of Social Studies students’ creativity skill development in Upper Basic Schools in Kwara State. It explored the profile of Social Studies teacher factors, the level of creativity skill development among students, and the influence of teacher factors on students’ creativity skills. The study adopted a descriptive survey design, with a population of junior secondary school students in Kwara State. A sample of 300 students from public upper basic schools across the three senatorial districts was selected using stratified random sampling. Data were collected using a validated questionnaire titled "Impact of Teacher Factors on Upper Basic Students’ Creativity Skills Development in Social Studies in Kwara State." The data were analysed using percentages, mean, standard deviation, weighted mean, and multiple linear regression analysis. The findings revealed that the profile of Social Studies teacher factors in Kwara State was average (Weighted Mean = 3.25). Similarly, creativity skill development among Upper Basic students in Social Studies was also at an average level (Weighted Mean = 2.85). A significant relationship was found between teacher factors and students’ creativity skill development (F = 9.227; p < 0.05), indicating that teacher factors play a crucial role in fostering creativity among students. The study concluded that teacher factors are significant determinants of Social Studies students’ creativity skill development in Kwara State. It recommended that school management should make appropriate and adequate investments in the education sector to provide necessary facilities and manpower. This would enhance students’ creative potential and improve learning outcomes in Social Studies.